The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
The following values have no corresponding Zotero field: accession-num: 16182861
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors